BANGLADESHI WORKING MOTHERS’ WORK-LIFE EXPERIENCE - (:unkn) unknown (My University, 2024)
This qualitative study explores the experiences of educated working mothers in Dhaka, Bangladesh, focusing on challenges encountered and the communication strategies they utilized for managing work-life boundaries. Grounded in Clark’s (2000) work-family border theory, an in-depth interview study with nine participants was conducted. Key findings of the thematic analysis highlight that the challenges faced by Bangladeshi working mothers are influenced by societal expectations, familial pressures, and workplace dynamics about boundary management. Participants navigated these challenges using various communication strategies, such as directly requesting childcare support from extended family members, communicating work schedules with family, having purposeful conversations with their spouse, and disclosing personal information to workplace supervisors. The findings underscore the critical need for communication strategies that acknowledge cultural norms and organizational barriers to facilitate effective work-life boundary management for working mothers in Bangladesh. The study implications suggest the initiative of workplace daycare facilities and family-friendly workplace policies, also highlighting the Bangladeshi working mothers’ role as models for their children to contribute to societal progress toward gender equality. The study also identifies areas for future research, including exploring the intersection of boundary management with mental health, marital relationships, and societal shifts influenced by increasing female workforce participation in Bangladesh.
Keywords: Bangladesh; Dhaka; Ideal mother; Work-family border theory; Work-life conflict; Working mothers